Exhaled breath and fecal volatile organic biomarkers of chronic kidney disease - Meinardi, Simone; Jin, Kyu-Bok; Barletta, Barbara; Blake, Donald R.; Vaziri, Nosratola D. (Biochimica et biophysica acta, 2013)
While much is known about the effect of chronic kidney disease (CKD) on composition of body fluids little is known regarding its impact on the gases found in exhaled breath or produced by intestinal microbiome. We have recently shown significant changes in the composition of intestinal microbiome in humans and animals with CKD. This study tested the hypothesis that uremia-induced changes in cellular metabolism and intestinal microbiome may modify the volatile organic metabolites found in the exhaled breath or generated by intestinal flora. SD rats were randomized to CKD (5/6 nephrectomy) or control (sham operation) groups. Exhaled breath was collected by enclosing each animal in a glass chamber flushed with clean air, then sealed for 45min and the trapped air collected. Feces were collected, dissolved in pure water, incubated at 37°C in glass reactors for 24h and the trapped air collected. Collected gases were analyzed by gas chromatography. Over 50 gases were detected in the exhaled breath and 36 in cultured feces. Four gases in exhaled breath and 4 generated by cultured feces were significantly different in the two groups. The exhaled breath in CKD rats showed an early rise in isoprene and a late fall in linear aldehydes. The CKD animals' cultured feces released larger amounts of dimethyldisulfide, dimethyltrisulfide, and two thioesters. CKD significantly changes the composition of exhaled breath and gaseous products of intestinal flora. Analysis of breath and bowel gases may provide useful biomarkers for detection and progression of CKD and its complications. ► Uremia changes the gut microbiome which is a major source of several toxic solutes. ► Effect of uremia on gaseous byproducts of microbiome is unknown and was studied here. ► Over 50 gases were detected in rats' exhaled breath and 36 gases in rats' cultured feces. ► Several fecal and exhaled breath gases were different between uremic and control rats. ► Value of these gases as biomarkers of kidney disease requires further investigation.